Better Sleep in a Strange Bed? Sleep Quality in South African Women with Posttraumatic Stress Disorder - Lipinska, Gosia; Thomas, Kevin G. F. (Frontiers in Psychology, 2017)
Although individuals diagnosed with posttraumatic stress disorder (PTSD) regularly report subjective sleep disruption, many studies using objective measures (e.g., polysomnography) report no PTSD-related sleep disruption. To account for these inconsistencies, some authors hypothesize that PTSD-diagnosed individuals have sleep-state misperception; that is, they self-report experiencing poor sleep quality, but objectively sleep relatively normally. We tested this sleep-state misperception hypothesis, collecting data on subjectively-reported sleep quality (in the home, and in the laboratory) and on objectively-measured, laboratory-based, sleep quality in PTSD-diagnosed participants from low socioeconomic status South African communities. Women with PTSD (n = 21), with trauma exposure but no PTSD (TE; n = 19), and healthy controls (HC; n = 20) completed questionnaires on their average sleep quality in the past 30 days, and on their sleep quality after a night (8 hours) of polysomnographic-monitored sleep in the laboratory. PTSD-diagnosed individuals reported poorer everyday subjective sleep quality than TE and HC individuals. In the laboratory, however, there were no between-group differences in subjective sleep quality, and few between-group differences in objective sleep quality (PTSD-diagnosed individuals only had decreased sleep depth). Furthermore, whereas measures of laboratory-based objective and subjective sleep quality correlated significantly, especially in PTSD-diagnosed individuals, there were few significant associations between objective sleep measures and everyday subjective sleep quality. Taken together, these findings suggest that PTSD-diagnosed individuals likely experienced better sleep quality in the laboratory than at home. Descriptive observations corroborated this interpretation, with almost half the sample rating their laboratory sleep (which they described as “safe” and “quiet”) as better than their home sleep (which was experienced in an atmosphere marked by high levels of violence and nighttime noise). These findings disconfirm the sleep-state misperception hypothesis as related to PTSD, and suggest that the laboratory environment may influence sleep quality positively in these individuals. Many investigations of sleep in PTSD do not consider the influence of the laboratory environment. Our findings suggest that future studies in this field should consider that sleep-state misperception may be an artefact of the laboratory setting, especially when samples are drawn from communities where violence and crime are an everyday reality.